Constitutional Resilience in the Era of Digital Governance: Legal Challenges of Algorithmic Decision-Making in Public Administration - Dian Kharisma (Universitas Sains dan Teknologi Komputer, 2026)
The expansion of algorithmic governance in public administration has transformed the exercise of administrative power in the digital era. The increasing use of artificial intelligence (AI) in administrative decision-making improves bureaucratic efficiency while generating constitutional challenges related to transparency, accountability, due process, judicial oversight, and fundamental rights protection. This study examines the constitutional implications of algorithmic decision-making and the capacity of constitutional frameworks to preserve the rule of law in digital governance. This research employs a normative juridical method combined with comparative constitutional analysis of AI governance approaches in the European Union, the United States, and several Asian jurisdictions. The findings reveal that algorithmic decision-making has transformed AI into a mechanism of public authority capable of reshaping state–citizen relations. The opacity of black-box systems , algorithmic bias, and the diffusion of administrative responsibility potentially weaken legality, democratic accountability, and judicial control in public administration. Comparative analysis demonstrates that different jurisdictions adopt distinct constitutional approaches to AI governance despite facing similar challenges in maintaining constitutional legitimacy within automated governance systems. This study proposes constitutional resilience as a normative framework for controlling algorithmic administrative power through transparency, human oversight, independent auditing, the right to explanation, and strengthened judicial review. The study contributes to the development of digital constitutionalism by reconstructing the relationship between technology, administrative authority, and constitutional principles in AI-driven governance.